Dari Teks ke Praktik Sosial: Rekonstruksi Usul Al-Fiqh Ulama Nusantara dalam Perspektif Antropologi - Nasution, Pangeran Putra Perkasa Alam; Daengparani, Abdul Rahman (Program Studi Sosiologi Agama Fakultas Ushuluddin, Adab dan Dakwah IAIN Manado, 2025)
This article examines the characteristics of Nusantara ulama’s fiqh through an Islamic anthropology approach combined with a reconstruction of contemporary uṣūl al-fiqh. The study addresses the academic problem of the dominance of normative-doctrinal approaches in fiqh studies that often neglect the social, cultural, and ethical dimensions of Islamic legal practices in non-Arab Muslim societies. Employing a qualitative hybrid approach, this research analyzes contemporary fiqh texts and ulama discourses using discourse analysis and normative-reflective readings of ‘urf, maqāṣid al-sharī‘ah, Sufism, and collective ijtihad. The findings reveal that Nusantara fiqh functions as a dynamic socio-religious practice, produced through negotiations between Islamic norms, local customs, and the needs of a plural society. The integration of Sufism strengthens the ethical dimension of fiqh, while collective ijtihad and the recognition of ‘urf serve as the epistemological foundations that ensure social legitimacy and contextual relevance. This article contributes to the development of sociology of religion and Islamic anthropology by offering an integrative framework for understanding fiqh as a lived and socially embedded practice.